Complications of Implant Rehabilitation in Ectodermal Dysplasia Patients: A Review Study - A Hassani; M Kakoienejad; P Bahmani; H Bahrani (Islamic Azad University, 2018)
Background and Aim: Ectodermal dysplasia (ED) is a hereditary disease that affects ectodermal tissues. Its oral manifestations include hypodontia or oligodontia, which cause the reduction of the height and width of the alveolar ridge. Considering numerous difficulties that these patients encounter with regard to facial appearance, talking, and chewing, their rehabilitation has a major influence on their quality of life. Implantation therapy is considered as a successful therapeutic protocol for substitution of such teeth. This article is a review of implant rehabilitation of ED patients and the related management procedures. Materials and Methods: In the present review article, the English articles in PubMed, ScienceDirect, MEDLINE, and Google Scholar databases from January 2000 to December 2017 have been investigated using the following keywords: anodontia, dental implants, ectodermal dysplasia, and hypodontia.  Conclusion: There is a multilateral approach to the treatment of ED patients according to their age, the status of oral soft and hard tissues and the remaining teeth. Implantation therapy for such patients is similar to that of non-ED patients.